Potential impacts of COVID-19 on regions and cities of the EU. - Böhme, Kai; Besana, Flavio; Lüer, Christian; Holstein, Frank; Hans, Sebastian; Valenza, Alessandro; Caillaud, Bertille; Derszniak-Noirjean, Martyna (My University, 2020)
What potential impacts will the COVID-19 pandemic have on regions and cities in the EU? Based on COVID-19 outbreaks, lockdown policies and the debate on recovery measures as at June 2020, this report provides some answers. It helps build a better understanding of the territorial dimension of COVID-19 policy responses. It also looks to contribute to shaping EU recovery measures that appropriately reflect Europe’s territorial diversity, the need for a recovery in line with the UN Sustainable Development Goals (SDGs) and for a multilevel governance approach.
Keywords: Virus; Krisensituation; Auswirkung; Wirtschaftsentwicklung; Konjunkturbelebung; Förderungsprogramm; Wirtschaftsförderung; Resilienz; Nachhaltige Raumentwicklung; Corona-Krise; Pandemie; Sustainable Devolopment Goals